Maurizio has left the building - Ferrari, Pierpaolo; Mastroeni, Sebastiano; Corbetta, Caroline; Guggenheim Museum, New York (Milan : Le Dictateur Press, 2012)
Hailed simultaneously as a provocateur, prankster, and tragic poet of our times, Maurizio Cattelan (b.1960) has created some of the most unforgettable images in recent contemporary art. These loose leaflets and stickers in a box are published on the occasion of Cattelan's retrospective at the Guggenheim in New York. All the photographs were taken in situ, thus giving a perfect impression of the spectacular method he used to exhibit his work.
Box set retrospective of an exhibition held at the Guggenheim New York, Nov. 4, 2011-Jan. 22, 2012.
Issued in box with a set of stickers.
boek
Keywords: Cattelan, Maurizio